The effectiveness of the bank lending channel: The role of banks' market power and business model - Muhammad Haseeb; Samanan Wattanapongphasuk; Kittisak Jermsittiparsert (Contemporary Economics, 2019)
This paper examines the effectiveness of the bank lending channel in a dual banking system in Malaysia, where both conventional and Islamic banks operate alongside each other. It also investigates the impact of bank competition on lending channels in financial systems. Using panel data from both Islamic and conventional banks in Malaysia, our findings indicate the ineffectiveness of the bank lending channel. Further, the empirical results suggest that the impact of monetary policy on bank lending does not depend on bank competition. In other words, the effectiveness of the lending transmission channel does not depend on the market power of the individual banks. Furthermore, the effectiveness of the lending channel appears to be independent of whether the bank is Islamic or conventional. This result is probably explained by the fact that the vast majority of Islamic banks in Malaysia are subsidiaries of conventional banks. Policymakers therefore do not need to differentiate between conventional and Islamic banks in regard to the effectiveness of the bank lending channel.
Keywords: G21; G28; 330; Bank competition; Bank lending channel; Dual banking system; Islamic banking; Monetary policy